Visual naming deficits in dyslexia: An ERP investigation of different processing domains. (October 2016) - Araújo, Susana; Faísca, Luís; Reis, Alexandra; Marques, J. Frederico; Petersson, Karl Magnus
Abstract: Naming speed deficits are well documented in developmental dyslexia, expressed by slower naming times and more errors in response to familiar items. Here we used event-related potentials (ERPs) to examine at what processing level the deficits in dyslexia emerge during a discrete-naming task. Dyslexic and skilled adult control readers performed a primed object-naming task, in which the relationship between the prime and the target was manipulated along perceptual, semantic and phonological dimensions. A 3×2 design that crossed Relationship Type (Visual, Phonemic Onset, and Semantic) with Relatedness (Related and Unrelated) was used. An attenuated N/P190 – indexing early visual processing – and N300 – which index late visual processing – was observed to pictures preceded by perceptually related (vs. unrelated) primes in the control but not in the dyslexic group. These findings suggest suboptimal processing in early stages of object processing in dyslexia, when integration and mapping of perceptual information to a more form-specific percept in memory take place. On the other hand, both groups showed an N400 effect associated with semantically related pictures (vs. unrelated), taken to reflect intact integration of semantic similarities in both dyslexic and control readers. We also found an electrophysiological effect of phonological priming in the N400 range – that is, an attenuated N400 to objects preceded by phonemic related primes vs. unrelated – while it showed a more widespread distributed and more pronounced over the right hemisphere in the dyslexics. Topographic differences between groups might have originated from a word form encoding process with different characteristics in dyslexics compared to control readers. Highlights: Visual naming deficits in dyslexia. Suboptimal integration and mapping of perceptual information to a form-specific percept in memory in dyslexia. Intact integration of semantic similarities. Deviant, atypical, phonological processing in dyslexic readers.